Aboveground biomass characterization of young plantation grown kawayan tinik (Bambusa blumeana J.A. & J.H. Schultes) in Nueva Ecija, Philippines for bioenergy production - Mendoza, Rosalie C.; Razal, Ramon A.; Abasolo, Willie P.; Visco, Roberto G.; Predo, Canesio D (2019)
This study assessed the potential of young kawayan tinik (Bambusa blumeana J.A. & J.H. Schultes) plantation for energy production by determining changes in biomass and calorific content over a three-year period. Yearly determination of biomass and culm growth was done for the plantation in Fort Magsaysay Military Reservation (FMMR) in Nueva Ecija, Philippines, by harvesting entire aboveground culms and non-culm portions of the plant. Culms were separated from branches and leaves and culm dimensions, height and diameter, and mass were obtained for both the culm and non-culm portions. Basal clump diameter was also measured and the number of culms per clump was counted. The chemical properties (volatile matter, fixed carbon, and ash) of the culm and the branches plus leaves (B+L) were likewise determined. Calculations were done for individual culm and total aboveground dry biomass per clump. Analysis of variance showed that both basal clump diameter and culm height were significantly affected by clump age, while culm number per clump and culm diameter did not vary significantly from year to year. Aboveground dry biomass increased with clump age. Chemical properties except for the ash content of the culms were all significantly affected by clump age. Analysis of variance also showed significant effect of clump age to the measured gross calorific values (GCVs) of culms while the corresponding value for B+L samples did not vary with clump age. (Author's abstract)
Includes bibliographical references (pages 634-636)
Keywords: Aboveground biomass; Bioenergy; Chemical properties; Culm characteristics; Gross calorific value; kawayan tinik